Correlação entre função ventricular direita e capacidade funcional em pacientes com cardiopatia chagásica crônica - Francilu Rodrigues Beloti (2008)
Chronic Chagas heart disease constitutes the most severe manifestation of Chagas disease, with great heterogeneity in its clinical presentation. The degree of myocardial dysfunction is a prognostic factor, but with no direct relation with the functional class. The present study evaluated the correlation between functional capacity and right ventricular function in patients with chronic Chagas heart disease. Sixty-five patients with chronic Chagas heart disease, clinically classified as stage IV and V, were selected in the absence of pacemaker. All patients were clinicallystable, in NYHA functional class I and II. History and physical examination were obtained looking for evidence of systemic and/or pulmonary congestion. A 12-lead electrocardiogram was performed in every patient and evaluated according to the standard criteria for Chagas disease.On the echocardiogram, measurements of the ventricular diameters andassessment of diastolic and systolic function of the left ventricle, including parameters based on tissue Doppler were performed. The right ventricle was assessed using a variety of techniques, such as M Mode diastolic diameter, diastolic area, quantitative analysis of contractility, degree of dilatation in comparison with the left ventricle, Tei index and tissue Doppler variables. Functional capacity was assessed with the exercise test, following the Bruce protocol, obtaining peak VO2. Other variables analyzed during the treadmill test were stress-induced arrhythmias, chronotropic incompetence and abnormal blood pressureresponse. A total of 65 patients was selected, with a mean age of 49 ± 9 years (28-68), with a predominance of male gender (60%). Twelve patients (18%) showed clinical evidence of right ventricular failure. The most prevalent ECG alteration was right bundle branch block associated with left anterior fascicle block, present in 66% of the cases.Stress-induced cardiac arrhythmias were frequent, developing in 51 patients (78%), especially rare isolated ventricular extrasystoles (53% of the cases). Forty-one patients (63%) had chronotropic incompetence, with no relation to the medication being used. Left ventricle dilatation, assessed by the diastolic diameter indexed by body surface area, was seen in 89% of the cases, with an ejection fraction of 44 ± 11%. Uponqualitative analysis of contractility and dilatation, the right ventricle was compromised in 19 patients (29%), but more than of half of the patients (52%) had a Tei index above the upper normal limit (0.32). There was no evidence of statistically significant correlation between peak VO2 and ejection fraction or other parameters of left ventricular systolic function, as the Tei index. In contrast, diastolic function parameters, such as E/E ratio, filling pressure markers, were associated with peak VO2. Likewise, ecocardiographic parameters that evaluate right ventricle correlated with peak VO2, such as tissue Doppler S wave and Tei index. On the multiple linear regression, sex, age, and right ventricular function, assessed by the tissue Doppler S wave, independently correlated with the peak VO2.This study demonstrated that right ventricular function, assessed by tissue Doppler, was the main determinant of functional capacity in patients with chronic Chagas heart disease, independent of age and sex.